Isolation of a novel glycyrrhizin metabolite as a causal candidate compound for pseudoaldosteronism - Morinaga, Osamu; Ishiuchi, Kan’ichiro; Ohkita, Takeshi; Tian, Chuanting; Hirasawa, Asuka; Mitamura, Miaki; Maki, Yasuhito; Yasujima, Tomoya; Yuasa, Hiroaki; Makino, Toshiaki (Scientific Reports, 2018)
Pseudoaldosteronism is a common adverse effect associated with traditional Japanese Kampo medicines. The pathogenesis is mainly caused by 3-monoglucuronyl glycyrrhetinic acid (3MGA), one of the metabolites of glycyrrhizin (GL) contained in licorice. We developed an anti-3MGA monoclonal antibody (MAb) and an ELISA system to easily detect 3MGA in the plasma and urine of the patients. However, we found that some metabolites of GL cross-reacted with this MAb. Mrp2-deficient Eisai Hyperbilirubinemia rats (EHBRs) were administered glycyrrhetinic acid (GA), and we isolated 22α-hydroxy-18β-glycyrrhetyl-3-O-sulfate-30-glucuronide (1) from the pooled urine with the guidance of positive immunostaining of eastern blot as the new metabolite of GL. The IC50 of 1 for type 2 11β-hydroxysteroid dehydrogenase (11β-HSD2) was 2.0 µM. Similar plasma concentrations of 1 and GA were observed 12 h after oral administration of GA to EHBR. Compound 1 was eliminated via urine, whereas GA was not. In Sprague–Dawley (SD) rats orally treated with GA, compound 1 was absent from both the plasma and the urine. Compound 1 was actively transported into cells via OAT1 and OAT3, whereas GA was not. Compound 1, when produced in Mrp2-deficiency, represents a potential causative agent of pseudoaldosteronism, and might be used as a biomarker to prevent the adverse effect.